How Can Green Innovation Strategy Enhance Higher Education Green Performance? Insights from Indonesia - Agus Alwindrajudi; Agus Rahayu; Syamsul Hadi Senin; Chairul Furqon; Asep Munawar; Stacy Leigh Scott (Jurnal Ilmu Pendidikan, 2025)
This study aims to describe the implementation of a green innovation strategy (GIS) to enhance university performance. A qualitative case study approach was employed. The research was conducted at a private higher education institution in Indonesia over a period of 91 days. 9 participants selected through purposive sampling took part in the study. Triangulation was adopted to compile holistic data on contextual phenomena. Thematic analysis was carried out with the support of NVivo. The findings shows that the GIS was implemented through: (1) the formulation of a GIS aligned with the university’s vision and characteristics; (2) the implementation of the GIS; and (3) a strong environment-based managerial focus. Taken together, these three components have been shown to improve three green higher education performance indicators; Academic-Tridharma Indicators, Operational-Campus Environment Indicators, and Campus Governance and Participation Indicators. These results are highly valuable because they capture the successful enhancement of Higher Education Green Performance amid the widespread lag in performance improvements among universities, and also highly relevant to the targets of developing sustainable campuses. This opens up the possibility for the study to be adapted by other higher education in various developing countries around the world.